Modelagem da dinâmica do uso e cobertura da terra do parque nacional da chapada das mesas, Maranhão, com vistas a conservação. - ROCHA, Hauanen Araújo (2022)
This work is an integral part of research carried out in the Conservation Unit called Chapada das Mesas National Park (PNCM), located in the municipalities of Estreito, Carolina and Riachão, in the state of Maranhão. The park was established in a panorama of wealth biological and natural attributes, acting as an ecotone between the Cerrado, Amazon and Caatinga biomes. O The study aims to: 1- quantify the use and coverage of land in the Chapada das National Park Tables for the years 2007 and 2014, 2014 and 2020, 2007 and 2020 using satellite images (Landsat7 ETM sensor and Landsat8 OLI sensor). 2- Investigate what are the main factors responsible for coverage changes for the study area; 3- Prepare a map of land use and coverage of the space PNCM; 4- Validate the model by comparing the prediction of changes for 2020 and the images classified for the same year; and 5- Obtain a projection of the usage and coverage situation for 2030. The study was carried out using the GIS program (SPRING, QGIS) and Dinamica EGO 7.1.1, a software free from environmental modeling. Through the use of computational methods and tools, such as geoprocessing, remote sensing and environmental modeling, the study was carried out throughout the area of the PNCM, making it possible to determine the factors that are causing environmental impacts within the study area. The research contributed to the management and monitoring of the PNCM, one of the largest richness of the cerrado biome ecosystem existing in the state of Maranhão, in addition to subsidizing and stimulate future research aimed at decision makers with a view to protecting and conservation of the Chapada das Mesas National Park.